Survey of neonatal respiratory care and surfactant administration in very preterm infants in the Italian Neonatal Network - Bellù, R.; Gagliardi, L.; Tagliabue, et al., P. (Acta Biomedica Atenei Parmensis, 2013)
Introduction: Variation of respiratory care is described between centers around the world.The Italian Neonatal Network (INN), as a national group of the Vermont-Oxford Network (VON) allows to perform a wide analysis of respiratory care in very low birth weight infants. Methods:We analyzed the dataset of infants enrolled in the INN in 2009 and 2010 and, for surfactant administration only, from 2006 to 2010 from 83 participating centers. All definitions are those of the (VON). A questionnaire analysis was also performed with a questionnaire on centers practices. Results: We report data for 8297 infants. Data on ventilator practices and outcomes are outlined. Variation for both practices and outcome is found. Trend in surfactant administration is also analyzed. Conclusions. The great variation across hospitals in all the surveyed techniques points to the possibility of implementing potentially better practices with the aim of reducing unwanted variation. These data also show the power of large neonatal networks in identifying areas for potential improvement.